A Pt-free pristine monolithic carbon aerogel counter electrode for dye-sensitized solar cells: up to 20% under dim light illumination. Issue 26 (29th May 2019) - Huang, Yi-June; Lin, Yong-Jie; Chien, Hung-Jei; Lin, Yi-Feng; Ho, Kuo-Chuan
Abstract : The best carbon aerogel CE gives an η of 9.08% at 100 mW cm −2 and 20.1% at 2.18 mW cm −2 . Abstract : In this work, pristine carbon aerogels (CAs) were used as Pt-free counter electrodes (CEs) in dye-sensitized solar cells (DSSCs) by varying the molar ratio of their precursors. Pristine mesoporous CAs with controlled resorcinol (R)/formaldehyde (F) and resorcinol (R)/sodium carbonate (C) molar ratios were successfully prepared. The as-prepared CAs were synthesized via a polymeric sol–gel reaction and were labeled as CA-O, CA-Q, CA-F, CA-C, and CA-G. The DSSCs using the as-prepared CA-C CE gave the best power conversion efficiency (PCE, η ), 9.08 ± 0.01%, among all the CA CEs. The CA-C CE is further applied to an indoor T5 light source system with an impressive η value of 20.1 ± 0.60% at 2.18 mW cm −2 (T5 lamp with 7000 lux). Moreover, the hardness of CA-C CE is 3.01 GPa (Brinell hardness test), which is comparable to that of the FTO/glass substrate. As a result, the CA-C CE shows great potential to replace traditional CEs based on the Pt/FTO/glass in DSSCs.